2012
DOI: 10.5432/ijshs.201118
|View full text |Cite
|
Sign up to set email alerts
|

Association of School Teachers' Occupational and Daily Physical Activity Level in Hong Kong

Abstract: The aims of the study were to examine the association between occupational PA and overall PA level of school teachers, and to compare the occupational PA level of school teachers engaged in PAs of a diŠerent nature at work (PE and non-PE teacher) in Hong Kong. Seventy-one elementary school teachers were assessed for three-day PA levels using step pedometers. Results indicated that occupational PA signiˆcantly predicted overall daily PA level. PE teachers were reported to have higher step counts during working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…This can be explained by the predominance of females in this study, and it is known that the prevalence of obesity is higher among the female gender [ 34 ]. In addition, the teaching profession is a sedentary occupation as it requires prolonged periods of static postures such as sitting and standing and teachers usually work for longer hours than required which restrict their physical activity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the predominance of females in this study, and it is known that the prevalence of obesity is higher among the female gender [ 34 ]. In addition, the teaching profession is a sedentary occupation as it requires prolonged periods of static postures such as sitting and standing and teachers usually work for longer hours than required which restrict their physical activity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in which accelerometers were not used also provide support for this argument. Cheung and Chow [12] found that physical education (PE) teachers had higher step counts during work hours compared with non-PE teachers. Sena, Pontes, Ferreira and Silva [13] found that in relation to the pattern of physical activity analyzed by the International Physical Activity Questionnaire (IPAQ), all of the postmen in their study were classified as active, whereas only 19% of the taxi drivers were classified as such.…”
Section: Litterature Reviewmentioning
confidence: 99%
“…When Thorp et al [8] and Parry and Straker [13] showed that workers in sedentary occupations spent 1.9% and 2.9%, respectively, of the work time at the MVPA level, their results contribute little to study the potential work has to the contribution of MVPA. However, some other studies using self-report questionnaires and pedometer readings have studied the contribution of physical activity at work in greater detail by comparing sedentary professions with more physically demanding professions [11,12,13,14]. All these studies showed that physically demanding professions contributed more to daily physical activity than less physically demanding jobs.…”
Section: The Importance Of Physical Activity During Workmentioning
confidence: 99%
“…Teachers oftentimes work extra hours to prepare for the next day, which might make it difficult for them to find time to engage in PA [13]. Studies about teachers' PA levels are scarce, but some have been conducted among public school teachers around the world [8,[14][15][16][17][18][19][20]. Studies in Brazil found the prevalence of 46-55% of low activity and sedentary behaviour among public school teachers [8,14,16], the prevalence was even higher among male teachers, reaching 69.5% [8].…”
Section: Introductionmentioning
confidence: 99%